Modelling the life cycle of machines that accumulate hidden damage - Становский, Александр Леонидович; Щедров, Игорь Николаевич; Торопенко, Алла Владимировна (Technology audit and production reserves, 2014)
A model of damage accumulation of the node structure of a complex machine during its operation is developed. In predicting the lifecycle of complex technical structure at its design stage, “passport” structure of analyzed option, data of bench tests of trial sample and also statistical information on external conditions and “behavior” during field testing and operation of products-analogues are used as the initial information. Such versatility and diversity of the model allows to consider inaccessible to observation parts of the object since the state of the latter indirectly affects the processes in accessible parts. On the example of a trailer welded frame, the problem of modeling the life cycle of complex technical system in mechanical engineering is considered. Mathematical apparatus of the automatic classification of data about the current state of the system to construct a model of damage accumulation in the frame is proposed.